Measurement of Secreted Embryonic Alkaline Phosphatase - Meiyan Wang; Xinyi Wang; Haifeng Ye (Bio-Protocol, 2023)
Secreted reporters have been demonstrated to be simple and useful tools for analyzing transcriptional regulation in mammalian cells. The distinctive feature of these assays is the ability to detect reporter gene expression in the culture supernatant without affecting the cell physiology or leading to cell lysis, which allows repeated experimentation and sampling of the culture medium using the same cell cultures. Secreted embryonic alkaline phosphatase (SEAP) is one of the most widely used reporter, which can be easily detected using colorimetry following incubation with a substrate, such as p-nitrophenol phosphate. In this report, we present detailed procedures for detection and quantification of the SEAP reporter. We believe that this step-by-step protocol can be easily used by researchers to monitor and measure molecular genetic events in a variety of mammalian cells due to its simplicity and ease of handling.Graphical abstractSchematic overview of the workflow described in this protocol